2014
DOI: 10.1111/jog.12447
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glucose transporter protein 1 and p63 in serous ovarian tumor

Abstract: Our findings show a progressive increase in the expression of GLUT1 and p63 from the benign serous cystadenomas, borderline cystadenomas to cystadenocarcinomas. Overexpression of GLUT1 and p63 are associated with the histology FIGO stage and metastasis of the tumors. These data suggested that the expression of GLUT1 and p63 may be closely related to the malignant transformation of serous ovarian tumors. However, the relative importance of GLUT1 and p63 in ovarian serous tumor development and tumorigenesis rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…We found a gradual increase in staining intensity of GLUT-1 from borderline to malignant tumors with a statistically significant difference supporting that the expression of this transporter may be closely related to the malignant transformation of epithelial ovarian tumors. Our findings agreed with results of other studies (3,7,8,9,10,12).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found a gradual increase in staining intensity of GLUT-1 from borderline to malignant tumors with a statistically significant difference supporting that the expression of this transporter may be closely related to the malignant transformation of epithelial ovarian tumors. Our findings agreed with results of other studies (3,7,8,9,10,12).…”
Section: Discussionsupporting
confidence: 93%
“…As regard the FIGO staging, there has been significant correlation with staining intensity for GLUT-1 (P = 0.01) which agreed with other authors (4,7,11). On the other hand, Canturia et al (14) found no statistical association between GLUT-1 expression levels and FIGO staging.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[3] Of the two different classes of hexose transporters (SGLT: sodium-dependent glucoset ransporter,G LUT:f acilitative glucose transporter [4] )t he GLUTsw ere found to be overexpressed in many tumors. [5] In particular, GLUT1 overexpression has been reported in many types of human cancers, including those of brain, [6] breast, [7] colon, [8] kidney, [9] lung, [10] ovary, [11] and prostate, [12] and is correlated with advanced cancer stages and poor clinicalo utcomes. It was demonstrated that the activation of certain oncogenes like c-myc, [13] KRAS, [10] BRAF, [14] and p53, [15] and transcription factors like hypoxiai nducible factor-1a, [16] can induce the GLUT1 overexpression.…”
Section: Introductionmentioning
confidence: 99%
“…29 However, mixed data regarding p63 status in serous carcinoma has been reported. Whereas some studies have shown that p63 expression may occur in malignant serous carcinomas of the ovary, 30 other studies have suggested that p63 immunoreactivity may actually decrease with malignant progression in serous lesions. 31 In our analysis, only 2 of 17 immunostained cases (12%) of serous carcinoma demonstrated focal p63 expression-one nonproblematic case associated with conventional serous morphology and diffuse WT1 expression, and one more-challenging case that demonstrated nests of carcinoma cells reminiscent of urothelial carcinoma.…”
Section: Analysis Of An Immunohistochemical Panel For Ck7 Wt1 Upiimentioning
confidence: 96%